Analisis Kesiapan Remaja Menjadi Orang Tua Perspektif Hukum Positif dan Psikologi Islam - Athiyah Zakiyah; Nimas Ayu Jihan ‘Aatika; Mardlotillah, Nilna; Muhammad Hikam Manzis (Fakultas Syariah IAIN Madura, 2024)
This article aims to evaluate the extent to which early married couples are ready to become parents in Bugul Kidul District, Pasuruan City. Research shows that during the 2023-2024 period, there were 17 cases of early marriage in Bugul Kidul District, with Kepel District recording the highest number, namely 6 cases. Factors that encourage early marriage include social pressure, economic conditions, lack of education about reproductive health, and local culture. The impact of early marriage on readiness for parenthood is significant, with young couples often lacking in emotional, physical and financial maturity. This results in difficulties in parenting and problems in the couple's relationship. This research concludes that early marriage in Bugul Kidul District is a problem that requires serious attention from various parties. Comprehensive interventions are needed, including education about reproductive health, strengthening the family economy, and psychological assistance for young couples to increase their readiness to assume the role of parents.